Improving police responses to sexual abuse offences against British South Asian Women - Gill, Aisha K. (Feminist responses to injustices of the state and its institutions, 2024)
The policing of racially minoritized communities has a chequered history in the UK: institutional racism, over-policing and under-protection are rife. While several studies have been conducted on policing and race, little research has examined how the intersections of race, gender and policing may contribute to the low rate of sexual abuse reporting by racially minoritized women - this cannot be solely attributed to some aspects of community policing that still suffer from institutional racism, as the literature suggests. This chapter uses empirical research, conducted within a feminist framework, to examine these issues in relation to how four British police force areas currently respond to sexual abuse incidents involving female survivors from the British South Asian community. The chapter offers an intersectional feminist analysis of what more the police and other statutory agencies can do to increase sexual abuse reporting from British South Asian and other racially minoritized women.